Java How to Program - M. Deitel Harvey (Prentice Hall, 2001)
In Java How to Program, Fourth Edition the Deitels introduce the fundamentals of object-oriented programming in Java. The 4th edition includes an optional 180-page case study that introduces object-oriented design with the UML. Key 4th edition topics include: